The cytoplasmic domain of CD4 is sufficient for its down-regulation from the cell surface by human immunodeficiency virus type 1 Nef - Stephen J. Anderson; Marc E. Lenburg; Nathaniel R. Landau; J. Victor Garcia (1994)
Human immunodeficiency virus type 1 Nef down-regulates surface expression of murine and human CD4 but not human CD8. We recently reported that the cytoplasmic domain of CD4 is required for its down-regulation by Nef. Using a chimeric molecule composed of the extracellular and transmembrane domains of human CD8 fused to the cytoplasmic domain of human CD4, we show here that the cytoplasmic domain of CD4 is sufficient for down-regulation by Nef. Since the cytoplasmic domain of CD4 is also the site of its association with p56lck, we used a series of CD4 mutants to determine whether the regions of the cytoplasmic domain of CD4 required for down-regulation by Nef are the same as those required for p56lck binding. Our results indicate that the portion of the cytoplasmic domain required for the down-regulation of CD4 by Nef overlaps with the binding site of p56lck, but the cysteine residues which are essential for the association of CD4 with p56lck are not required. This observation raised the possibility that Nef competes with p56lck for binding to CD4. However, under conditions which are considerably milder than those permissive for coimmunoprecipitation of CD4 and p56lck, we found no evidence for an association between Nef and CD4. While a decrease in total CD4 was observed in lysates of cells expressing Nef, the levels of p56lck were not significantly affected. Pulse-chase experiments further revealed a decrease in the half-life of CD4 in Nef-expressing cells. These results show that the decrease in surface CD4 expression induced by Nef is mediated at least in part by a decrease in the half-life of CD4 protein. These results also indicate that a large portion of p56lck is free of CD4 in T cells expressing Nef, which could have a significant effect on T-cell function.